Novisque rebus inﬁdelis Allobrox (Hor. Epod. 16. 6) - Egorova, Sofia (Hyperboreus, 2019)
This paper is a discussion of the ﬁrst verses of Horace’s Epode 16, which lists the key enemies of the Romans, including the Allobroges tribe, described as novis rebus inﬁdelis. The proposal is to interpret the latter as a reference to the involvement of Allobrogical legates in the conspiracy of Catiline, whose supporters had just been unmasked with the help of the Gauls who had come down on the side of the Republic. The inconsistency (in style and logic) that appears in the Epode can be explained by Horace’s commitment to exaggeration, because the Gauls had proved to be unreliable even for the conspiracy (we propose to interpret novis rebus as dat. incommodi). The paper also includes two remarks on the statements found in some commentaries. First, Denis Lambin neither proposes the idea of the denomination of the Gauls overall in this fragment, nor does he support it. Second, there are no data on the uprising of the Allobroges in the 40s to 30s BC, which excludes the passage in question from those relevant for dating of the Epodes.